The Revision Procedure, the Role of the Constitutional Court in the Referendum Procedure and the President Dismissal - Ştefan Alexandru BĂIŞANU (Annals of Philosophy, Social and Human Disciplines, 2011)
The revision procedure combines specific techniques of the representative democracy with those specific to direct democracy, both by enshrining popular constitutional initiative, and by giving the social corpus the possibility to intervene at the end of the revision process towards a referendum. The Constitutional Court has no constitutional control on any laws resulting from the referendum. The referendum is actually a popular revocation, so the president is revoked, not dismissed.